Research progress of non-coding RNA in atrial fibrillation - Xue, Zongqian; Zhu, Jinbiao; Liu, Juan; Wang, Lingli; Ding, Jijun (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) is a common arrhythmia in clinic, and its incidence is increasing year by year. In today's increasingly prevalent society, ageing poses a huge challenge to global healthcare systems. AF not only affects patients' quality of life, but also causes thrombosis, heart failure and other complications in severe cases.Although there are some measures for the diagnosis and treatment of AF, specific serum markers and targeted therapy are still lacking. In recent years, ncRNAs have become a hot topic in cardiovascular disease research. These ncRNAs are not only involved in the occurrence and development of AF, but also in pathophysiological processes such as myocardial infarction and atherosclerosis, and are potential biomarkers of cardiovascular diseases. We believe that the understanding of the pathophysiological mechanism of AF and the study of diagnosis and treatment targets can form a more systematic diagnosis and treatment framework of AF and provide convenience for individuals with AF and the society.